Framework for Biodiversity Information Retrieval in Malaysia - Dhillon, Sarinder; Paunoo, Baldeve; Sidhu, Amandeep (Springer-Verlag, 2013)
A wealth of information exists on Malaysia’s biodiversity resources and associated knowledge. This may be in form of specimens, literature, and electronic databases. The problem currently faced by Malaysia in regards to all this information is basically one of dissemination and hence retrieval of this information in a networked environment. Presently there is no system to link the scattered data so as to facilitate exchange of data amongst the different databases available in the country. In this paper we developed an indigenous framework for integrating distributed heterogeneous and relational biodiversity databases to facilitate biodiversity data sharing among the scientific contemporaries especially in Malaysia. This proposed approach is expected to encourage interested members of the research community to work together while maintaining the privacy of their data. Simplicity is also stressed with the intention of offering a system which is adaptable to wide spectrum users within the scientific community in Malaysia and the rest of the world.